Miami Transformed : Rebuilding America One Neighborhood, One City at a Time - Diaz, Manny (Book collections on Project MUSE., 2013)
Former two-term mayor of Miami Manny Diaz shares lessons learned from governing one of America's most diverse and dynamic urban communities.